2016
DOI: 10.3389/fnins.2016.00128
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Over the Primary and Secondary Somatosensory Cortices Transiently Improves Tactile Spatial Discrimination in Stroke Patients

Abstract: In healthy subjects, dual hemisphere transcranial direct current stimulation (tDCS) over the primary (S1) and secondary somatosensory cortices (S2) has been found to transiently enhance tactile performance. However, the effect of dual hemisphere tDCS on tactile performance in stroke patients with sensory deficits remains unknown. The purpose of this study was to investigate whether dual hemisphere tDCS over S1 and S2 could enhance tactile discrimination in stroke patients. We employed a double-blind, crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
5
30
0
Order By: Relevance
“…Such perceptual judgments often depend on inhibition between primary sensory representations in cortex and thus tasks of this nature, maybe more easily be altered by tDCS than those requiring higher cognitive regions where the link between E-I balance and performance is less easy to intuit. Indeed, tDCS has been shown to alter somatosensory discrimination (Fujimoto et al 2016;Labbé et al 2016) and auditory pitch discrimination (Mathys et al 2010). Surprisingly, as far as we are aware, no authors have investigated whether tDCS can alter performance on a visual ODT, a task with clear links to E-I balance in cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Such perceptual judgments often depend on inhibition between primary sensory representations in cortex and thus tasks of this nature, maybe more easily be altered by tDCS than those requiring higher cognitive regions where the link between E-I balance and performance is less easy to intuit. Indeed, tDCS has been shown to alter somatosensory discrimination (Fujimoto et al 2016;Labbé et al 2016) and auditory pitch discrimination (Mathys et al 2010). Surprisingly, as far as we are aware, no authors have investigated whether tDCS can alter performance on a visual ODT, a task with clear links to E-I balance in cortex.…”
Section: Introductionmentioning
confidence: 99%
“…NIBS, which is repetitive TMS (rTMS) [96,98] and transcranial direct current stimulation (tDCS) [124], over the primary motor cortex can modulate the excitability of the motor cortex [125] and is often used as an effective tool for enhancing behavioral training after stroke with hemiplegia [125][126][127][128]. Furthermore, the NIBS to the cerebellum modulates cerebellar excitability [98,[129][130][131], motor function [132,133], and motor learning [32,[134][135][136][137][138] in healthy population.…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%
“…In other studies, contralateral c-tDCS reduced sensitivity to hot and cold sensations [16], decreased pain perception thresholds [17], and decrease tactile discrimination performance [18]. In a recent study, the tactile discrimination threshold of stroke patients was measured by GOT and it was shown that dual-hemispheric tDCS improved performance in comparison to a sham stimulation group [15] Similarly, low current a-tDCS over S1 of healthy young adults enhanced contralateral index finger discrimination performance in GOT, with no such effects in the s-tDCS condition [12].…”
mentioning
confidence: 93%
“…Positively charged stimulation, which causes depolarization of superficial cortical neurons, is named anodal-tDCS (a-tDCS) and negatively charged stimulation, which causes hyperpolarization, is named cathodal-tDCS (c-tDCS) [11]. Sham-tDCS (s-tDCS) is often used to control for the experimental setup itself both in applied [12] and clinical [13] research, but findings are ambivalent: while in some studies s-tDCS does not provide different results from active stimulations, which serves as evidence for a placebo effect [14], in other studies s-tDCS produces different results, refuting a placebo effect [15].…”
mentioning
confidence: 99%